Live-attenuated Japanese encephalitis virus inhibits glioblastoma growth and elicits potent antitumor immunity - Qi, Zhongbing; Zhao, Jing; Li, Yuhua; Zhang, Bin; Hu, Shichuan; Chen, Yanwei; Ma, Jinhu; Shu, Yongheng; Wang, Yunmeng; Cheng, Ping (Frontiers in Immunology, 2023)
Glioblastomas (GBMs) are highly aggressive brain tumors that have developed resistance to currently available conventional therapies, including surgery, radiation, and systemic chemotherapy. In this study, we investigated the safety of a live attenuated Japanese encephalitis vaccine strain (JEV-LAV) virus as an oncolytic virus for intracerebral injection in mice. We infected different GBM cell lines with JEV-LAV to investigate whether it had growth inhibitory effects on GBM cell lines in vitro. We used two models for evaluating the effect of JEV-LAV on GBM growth in mice. We investigated the antitumor immune mechanism of JEV-LAV through flow cytometry and immunohistochemistry. We explored the possibility of combining JEV-LAV with PD-L1 blocking therapy. This work suggested that JEV-LAV had oncolytic activity against GBM tumor cells in vitro and inhibited their growth in vivo. Mechanistically, JEV-LAV increased CD8+ T cell infiltration into tumor tissues and remodeled the immunosuppressive GBM microenvironment that is non-conducive to immunotherapy. Consequently, the results of combining JEV-LAV with immune checkpoint inhibitors indicated that JEV-LAV therapy improved the response of aPD-L1 blockade therapy against GBM. The safety of intracerebrally injected JEV-LAV in animals further supported the clinical use of JEV-LAV for GBM treatment.